Controlling wspomagany zintegrowanym systemem zarządzania klasy ERP w przedsiębiorstwie Alfa - Janczyk-Strzała, Elżbieta (ERP System as a Tool of Controlling in Alfa Company., 2006)
The process of globalization presents not only a lot of opportunities but also some threats for companies operating on its area. The changes have made many companies' existence much more complicated. They have to use modern methods of management. This article is dedicated to the significant role which ERP system plays in controlling. It describes its role in Alfa company.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1101, s. 161-169